(untitled) (Mongolian Journal of Agricultural Sciences, 2015)
The One Health concept recognizes that the health of humans is connected to the health of animals and the environment. The major aim of the One Health is to improve health and well-being through the prevention of risks and the mitigation of effects of crises that originate at the interface between humans, animals and their various environments. Regardless of which of the many definitions of One Health is used, the common theme is collaboration across sectors. Collaborating across sectors that have a direct or indirect impact on health involves thinking and working across silos and optimizing resources and efforts while respecting the autonomy of the various sectors. To improve the effectiveness of the One Health approach, there is a need to establish a better sectoral balance among existing groups and networks, especially between veterinarians and physicians, and to increase the participation of environmental and wildlife health practitioners, as well as social scientists and development actors. As this kind of collaboration newly introduced in Mongolia, there are numerous complications and difficulties may arise, that eventually could lead to the results, with higher negative impact to the public and personal health. From the technical perspective, it is undoubtfully important to evaluate the system and reveal the gap and weakness of each stakeholder in this important network and try to introduce common standard operational procedures for the handling and maintaining infective agents to avoid the unpleasant spill over the pathogen into the environment. Mongolian Journal of Agricultural Sciences Vol.13(2) 2014: 146-152